The Challenges of Higher Education Students in Balancing Work and Study Life at a Community College in Godawari Municipality, Nepal - Timalsina, Shanti; Katwal, Suman (Janabhawana Research Journal, 2025)
Higher education has become a dominant aspect of the modern world. Despite having the central role in Nepalese educational landscape, Tribhuvan university has witnessed persistent challenges characterized by low pass rate, low graduation rate and high dropout rate which makes an urgent need to examine the challenges of higher education. This study inspects the challenges faced by Nepalese higher education students in balancing work and studies. The study uses a descriptive approach, surveying 137 bachelor-level working students from a community campus in Lalitpur, Nepal. Data was collected through structured questionnaires and analyzed using IBM SPSS. The findings reveal that financial difficulties pose the major challenge, with majority of students depending on family assistance and a notable portion leaving their studies because of monetary issues. Academic challenges include insufficient practical training opportunities and widespread delays in examinations. Mental health concerns are prevalent, as majority of students experience stress, yet only a small fraction receive proper support. On the social front, disparities across regions and family pressures are major concerns. The study concludes that financial aid, better academic resources, and mental health support are needed. Policymakers and institutions must address these issues to maintain work-study balance for the students in Nepal.